2010
DOI: 10.1038/jhh.2010.22
|View full text |Cite
|
Sign up to set email alerts
|

Association of resistin and adiponectin with different clinical blood pressure phenotypes

Abstract: We investigated whether the resistin (Res) and adiponectin (Adp) levels are associated with different clinical blood pressure (BP) phenotypes. Among 465 consecutive never-treated white subjects, we excluded those with diabetes mellitus; impaired glucose metabolism; history of any cardiovascular disease or other concurrent medical condition; secondary hypertension; ongoing vasoactive treatment. Three separate clinic BP measurements and ambulatory BP monitoring were implemented to divide 328 subjects (aged 48±6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…Meanwhile, significant increases in BMI, random blood sugar, HbA1c, and resistin level were observed in the diabetic children compared with the control group (p < 0.0001). This agreed with a recent study of Yazıcı et al (28) that reported higher resistin levels in type-1 diabetic patients compared with the controls, as well as many other studies (29,30). Conversely, a previous work of Schäffler et al reported lower resistin concentrations in adult patients with type-1 diabetes compared with healthy control subjects with a similar age range.…”
Section: Discussionsupporting
confidence: 86%
“…Meanwhile, significant increases in BMI, random blood sugar, HbA1c, and resistin level were observed in the diabetic children compared with the control group (p < 0.0001). This agreed with a recent study of Yazıcı et al (28) that reported higher resistin levels in type-1 diabetic patients compared with the controls, as well as many other studies (29,30). Conversely, a previous work of Schäffler et al reported lower resistin concentrations in adult patients with type-1 diabetes compared with healthy control subjects with a similar age range.…”
Section: Discussionsupporting
confidence: 86%
“…That study performed ambulatory BP measurement on 328 untreated, non- proportion of the syndrome was higher in masked (29%) and sustained hypertension (30%) than in normotension (12%) or white-coat hypertension (17%). 15 The prevalence of harmonised MS was similar in the untreated Finn-Home study population and in the larger sample of the Health 2000 survey. 1 In the present study, MS was two to three times more common in masked and white-coat hypertension than in normotension when EGIR or harmonised definition was used.…”
Section: Insulin Resistancementioning
confidence: 85%
“…[14][15][16][17][18][19][20] Although the prevalence of MS varies widely depending on the definition used, only three studies reported criteria for the syndrome. [14][15][16] Only a Korean study defined masked hypertension using home BP measurement but it investigated treated hypertensive patients. [17][18][19] The majority of the previous studies did not find any significant differences in MS between the BP groups 14,16-20 but only one study investigated all four BP subgroups.…”
Section: Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…In two different outpatient samples, we have previously demonstrated that white-coat hypertension was not associated with either free leptin or adiponectin; however, both of these adipokines were associated with sustained and masked hypertension. 3,4 Consequently, we believe that white-coat phenomenon might not have affected the results of the Danish prospective study, 1 and this is further supported when harder criteria for the definition of the outcome were implemented (i.e., systolic BP ≥160 mm Hg and/or diastolic BP ≥95 mm Hg). In contrary, masked hypertension phenomenon would have diminished and convicted as not significant of the predictive value of leptin and adiponectin on incident hypertension, respectively.…”
mentioning
confidence: 96%